Profil Profil Kemampuan Literasi Sains Siswa SMP Berdasarkan Gender Menggunakan Model STEM: (Profil Scientific Literacy Ability of Junior High School Students Bades on Gender Using The STEM Models) - Syifa Nurazizah Syifa; Suhendar Suhendar; Gina Nuranti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
21-st century skills in education integrate literacy skills, knowledge, skills, and attitudes. One of them is scientific literacy. The scientific literacy ability of the students in Indonesia from 2000 to 2018, according to PISA (2018), is still below average. It is due to the lack of attention of Indonesian education on literacy skills which are actually necessary for everyday life. This research was conducted in 2022. The purpose was to determine the differences in the results of scientific literacy skills between male and female students in grade 2 of junior high school. This study uses the One Group Posttest Only design with technical data analysis using the posttest results that have been carried out by students, then calculated by looking at the average indicators of each question. The results showed that there were differences in the results of students' scientific literacy abilities between boys and girls. The increase in scientific literacy for female students is 82.2 and is in the very good category, and male students is 71.3 and is in the good category. With these differences, it can be concluded that scientific literacy skills using the STEM model for female students increased better than male students. Key words: Science Literacy, STEM, Gender Â ABSTRAK Keterampilan abad ke 21 dalam bidang pendidikan mengintergrasikan kemampuan literasi, pengetahuan, keterampilan, dan sikap. Salah satu keterampilan literasi dalam abad ke 21 yaitu kemampuan literasi sains. Kemampuan literasi sains siswa di Indonesia menurut PISA tahun 2018 sejak tahun 2000 sampai 2018 masih dibawah rata-rata. Hal ini disebabkan kurang perhatiannya dunia pendidikan di Indonesia terhadap kemampuan literasi yang mana penting untuk kehidupan sehari-hari. Penelitian ini dilakukan pada tahun 2022.Tujuan penelitian ini yaitu untuk mengetahui perbedaan hasil kemampuan literasi sains antara siswa laki-laki dan siswa perempuan di kelas 8 SMP. Penelitian ini menggunakan desain One Group Postest Only dengan teknis analisis data menggunakan hasil postest yang telah dilakukan oleh siswa yang kemudian dihitung dengan melihat rata-rata perindikator dari setiap soal. Hasil penelitian menunjukkan adanya perbedaan hasil kemampuan literasi sains siswa antara laki-laki dan perempuan. Peningkatan literasi sains siswa perempuan sebesar 82,2 dan masuk kedalam kategori sangat baik, dan untuk hasil literasi sains siswa laki-laki sebesar 71,3 dan masuk kedalam kategori baik. Dengan hasil perbedaan tersebut dapat dikatakan kemampuan literasi sains menggunakan model STEM untuk siswa perempuan meningkat lebih baik dibandingkan dengan siswa laki-laki. Kata kunci: Literasi Sains, STEM, Gender